Manipulation of Population Levels through Zeno-Type Measurements - Javier Contreras Sánchez; Fray de Landa Castillo-Alvarado; José Luis Hernández-Pozos (Photonics, 2023)
We present a scheme, based on Bloch equations and Zeno-type measurements, that allows the control of the probability density evolution of the eigenstates of a V-type system. The equations are solved numerically and we present how the population in each level can be controlled using different sequences of “pulse measurements”. The entropy between the “measurement device” and the field used to perform the measurement process is evaluated for different strengths of such field, these calculations show that the entropy is maximized when we are in the Zeno regime. The results shown here unveil different possible strategies for controlling the population levels of a V-type system and could be implemented, for example, in trapped ions or RMN qubits.